A flux-cored welding wire and its preparation method and application

By adding NiB and TiN to the flux-core welding wire and controlling its proportion, Ti-Ni-O oxide is formed, and the needle-shaped ferrite nuclei is induced, the problem of deterioration of the weld joint tissue and low low-temperature toughness in super-large line energy welding is solved, and the strength and low-temperature toughness of the weld metal are significantly improved.

CN119077211BActive Publication Date: 2025-04-15CHINA-UKRAINE INST OF WELDING GUANGDONG ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411356991.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-04-15
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

During the large-line energy welding process, the tissue of the welded joint deteriorates, resulting in poor tissue such as Weisite, which leads to a reduction in toughness of the welded joint and affects the safety of the workpiece. Especially under the conditions of super-large line energy welding (≥400kJ/cm), the effective inclusions are unstable, the grains are coarse, and the low-temperature toughness is low.

Method used

By adding NiB and TiN to the flux-core welding wire and appropriately adjusting the ratio of both, NiB and TiN are decomposed into free [Ni], [Ti], [B], [N] during the super-large line energy welding process, forming fine and dispersed Ti-Ni-O oxides, inducing a needle-like ferrite nucleus, inhibiting the growth of the original austenite grains, and improving the strength and toughness of the weld metal.

Benefits of technology

Under the condition of welding heat input ≥400kJ/cm, the strength and toughness of the weld metal is significantly improved, the low-temperature toughness is improved, the grain is refined, the tensile strength, yield strength and elongation of the weld joints are improved, and the pores and surface defects in the weld are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005063892440000091
    Figure BDA0005063892440000091
  • Figure BDA0005063892440000092
    Figure BDA0005063892440000092
  • Figure HDA0005063892450000011
    Figure HDA0005063892450000011
Patent Text Reader

Abstract

The invention belongs to the field of welding materials, and specifically discloses a flux-cored welding wire and a preparation method and application thereof, wherein the flux-cored welding wire comprises an outer skin and powder; the powder is filled in the outer skin; the powder comprises the following components in mass percentage: Mn 2.5-4.5%, Si 1-3%, Ca 0.001-0.005%, Mo 0.05-0.78%, V 0.005-0.15%, Cu 0.02-0.80%, Al 0.002-0.07%, TiN 0.3-0.55%, NiB 2.0-4.0%, slag forming agent 2.4-5.7%, Fe 81-91.7%. The flux-cored welding wire of the invention is used to weld engineering steel, which can significantly improve the mechanical strength of the weld, improve the toughness at body temperature and refine the grain size at the weld.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of welding materials, and in particular relates to a flux-cored welding wire and a preparation method and application thereof. Background Art

[0002] As a high energy density welding method, high energy input welding such as electro-gas welding (EGW) is suitable for welding thick plates and large-sized components. It has many advantages such as easy operation, fast welding speed, high quality, energy saving and high welding efficiency. It can be used for the efficient construction of large marine engineering equipment. However, due to the large heat input, high energy input welding will lead to the deterioration of the microstructure of the welded joint and produce undesirable microstructures such as widmanstattenite, thereby reducing the toughness of the welded joint and affecting the safety of the workpiece.

[0003] In the 1990s, Japanese scholars proposed oxide metallurgy technology, which adds alloy elements to the weld to control the number, type, size and distribution of inclusions in the weld metal, thereby promoting the nucleation of acicular ferrite and refining the original austenite grains to improve the strength and toughness of the weld metal.

[0004] CN109175773A discloses a flux-cored welding wire for bridge steel Q620qE, which is made of flux-cored powder wrapped with low-carbon cold-rolled steel strip, and the flux-cored powder accounts for 20% to 65% of the total mass of the welding wire. The flux-cored components and dosages are calculated by mass percentage as follows: 0.6% to 1.5% nano titanium nitride powder, 0.7% to 1.7% nano boron nitride powder, 0.5% to 0.8% nano chromium nitride powder, 0.3% to 0.5% nano graphene, 0.3% to 0.8% nano cerium oxide, FeBa 30 Si 35 Silicon-barium alloy 0.2% to 0.5%, Nb powder 0.2% to 0.35%, Ni powder 2.0% to 3.5%, Cu powder 0.2% to 0.45%, Mn powder 2.0% to 2.8%, SiF4 powder 1.8% to 3.0%, the remainder is FHT100·25 reduced iron powder, and the sum of the mass percentages of nano-titanium nitride, nano-boron nitride, and nano-chromium nitride must be ≤3.2%. Through the composite strengthening of multiple elements, the yield strength ratio is reduced, the low-temperature impact toughness is effectively improved, and the atmospheric corrosion resistance is enhanced while ensuring the use strength. However, the welding wire in the invention is only suitable for lower welding heat input (≤20kJ / cm). In the process of high-line energy welding, a large amount of titanium nitride, boron nitride, and chromium nitride particles added are very likely to cause cracks; in addition, due to the excessively high nitrogen content, the nitrogen element may volatilize to produce pores, resulting in reduced mechanical properties of the welded joint.

[0005] In summary, there have been some studies on the use of reasonable ratios of elements or the addition of nanoparticles to promote the nucleation of acicular ferrite or hinder the growth of austenite, and the strength or low-temperature toughness of the weld can be improved. However, with the development trend of increasingly large-scale marine equipment, high-energy line welding is also developing towards higher energy lines. For example, the actual welding energy of EGW can exceed 600kJ / cm. Under such high welding heat input, the high temperature residence time is longer and the peak temperature is higher, resulting in coarser original austenite grains. The effective inclusions under ordinary high-energy line welding conditions are no longer stable. Therefore, it is urgent to develop a flux-cored wire suitable for ultra-high energy line welding (≥400kJ / cm). Summary of the invention

[0006] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a flux-cored welding wire.

[0007] A second object of the present invention is to provide a method for preparing a flux-cored welding wire.

[0008] A third object of the present invention is to provide a welding method.

[0009] A fourth object of the present invention is to provide application of the above-mentioned flux-cored welding wire and / or the above-mentioned welding method in the field of welding.

[0010] In order to achieve the above object, the technical solution adopted by the present invention is:

[0011] The first aspect of the present invention provides a flux-cored welding wire, comprising an outer skin and powder; the outer skin is filled with powder; the powder comprises the following components in mass percentage: Mn 2.5-4.5%, Si 1-3%, Ca 0.001-0.005%, Mo0.05-0.78%, V 0.005-0.15%, Cu 0.02-0.80%, Al 0.002-0.07%, TiN 0.3-0.55%, NiB2.0-4.0%, slag forming agent 2.4-5.7%, Fe 81-91.7%.

[0012] Preferably, the powder is composed of the following components in mass percentage: Mn 2.5-4.5%, Si 1-3%, Ca0.001-0.005%, Mo 0.05-0.78%, V 0.005-0.15%, Cu 0.02-0.80%, Al 0.002-0.07%, TiN 0.3-0.55%, NiB 2.0-4.0%, slag forming agent 2.4-5.7%, and Fe as the balance.

[0013] The present invention adds NiB and TiN to the flux-cored welding wire and appropriately adjusts the ratio of the two. In the process of ultra-high wire energy twin-wire gas-electrode vertical welding, NiB and TiN will be decomposed into free [Ni], [Ti], [B], and [N]. Ti and Ni elements can be combined with O in the solidification process to form a large number of fine and dispersed Ti-Ni-O oxides, which induce the nucleation of needle-shaped ferrite, resulting in a longer path during crack propagation, increased crack propagation resistance, and improved toughness of the welded joint; in addition, the B element will be segregated at the grain boundary, inhibiting the growth of the original austenite grains and the formation of grain boundary ferrite, and N can be combined with Al, Ti and other elements in the steel to form nitrides and re-precipitate, thereby improving the strength of the weld metal.

[0014] Preferably, in the medicinal powder, the mass percentage of fluorite is not 0%.

[0015] In the medicinal powder of the present invention, the mass percentage of Mn is 2.5-4.5%, for example, it can be selected from 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5% or any point value in the range composed of any two end points of the above.

[0016] In the medicinal powder of the present invention, the mass percentage of Si is 1-3%, for example, it can be selected from 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3% or any point value in the range composed of any two end points of the above.

[0017] In the medicinal powder of the present invention, the mass percentage of Ca is 0.001-0.005%, for example, it can be selected from 0.001%, 0.002%, 0.003%, 0.004%, 0.005% or any point value in the range consisting of any two end points mentioned above.

[0018] In the medicinal powder of the present invention, the mass percentage of Mo is 0.05-0.78%, for example, it can be selected from 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.75%, 0.78% or any point value in the range composed of any two end points of the above.

[0019] In the medicinal powder of the present invention, the mass percentage of V is 0.005-0.15%, for example, it can be selected from 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.011%, 0.012%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15% or any point value in the range composed of any two end points of the above.

[0020] In the medicinal powder of the present invention, the mass percentage of Cu is 0.02-0.80%, for example, it can be selected from 0.02%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or any point value in the range consisting of any two end points of the above.

[0021] In the medicinal powder of the present invention, the mass percentage of Al is 0.002-0.07%, for example, it can be selected from 0.002%, 0.005%, 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045%, 0.05%, 0.055%, 0.06%, 0.065%, 0.07% or any point value in the range composed of any two end points of the above.

[0022] In the medicinal powder of the present invention, the mass percentage of TiN is 0.3-0.55%, for example, it can be selected from 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55% or any point value in the range composed of any two end points of the above.

[0023] In the medicinal powder of the present invention, the mass percentage of NiB is 2.0-4.0%, for example, it can be selected from 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4% or any point value in the range composed of any two end points of the above.

[0024] Preferably, the slag-forming agent includes at least one of rutile, fluorite, feldspar and mullite.

[0025] Preferably, based on the total mass percentage of the powder being 100%, the slag-forming agent comprises the following components in mass percentage: 1-1.4% rutile, ≤0.5% fluorite, 1-2.8% feldspar, and 0.4-1.0% mullite. In the present invention, rutile, fluorite, feldspar, and mullite constitute the slag-forming agent, which can stabilize the arc, adjust the melt viscosity, and protect the welding droplet and the molten pool.

[0026] Preferably, the medicinal powder is composed of the following components in mass percentage: Mn 2.5-4.5%, Si 1-3%, Ca0.001-0.005%, Mo 0.05-0.78%, V 0.005-0.15%, Cu 0.02-0.80%, Al 0.002-0.07%, TiN 0.3-0.55%, NiB 2.0-4.0%, rutile 1-1.4%, fluorite ≤0.5%, feldspar 1-2.8%, mullite 0.4-1.0%, and Fe as the balance.

[0027] In the medicinal powder of the present invention, the mass percentage of rutile is 1-1.4%, for example, it can be selected from 1%, 1.1%, 1.2%, 1.3%, 1.4% or any point value in the range consisting of any two end points of the above.

[0028] In the medicinal powder of the present invention, the mass percentage of fluorite is 0-0.5%, for example, it can be selected from 0.001%, 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.045%, 0.05%, 0.055%, 0.06%, 0.065%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or any point value in the range composed of any two end points of the above.

[0029] In the medicinal powder of the present invention, the mass percentage of feldspar is 1-2.8%, for example, it can be selected from 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8% or any point value in the range composed of any two end points of the above.

[0030] In the medicinal powder of the present invention, the mass percentage of mullite is 0.4-1.0%, for example, it can be selected from 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any point value in the range consisting of any two end points of the above.

[0031] Preferably, the material of the outer skin includes H08A alloy steel.

[0032] Preferably, the mass of the powder is 20-30% of the mass of the flux-cored welding wire, for example, it can be selected from 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any point value in the range composed of any two end points of the above.

[0033] Preferably, the diameter of the flux-cored welding wire is 1-2 mm, for example, can be selected from 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2 mm or any point value in the range formed by any two end points of the above.

[0034] The second aspect of the present invention provides a method for preparing the flux-cored welding wire according to the first aspect of the present invention, comprising the following steps:

[0035] The raw materials of the powder are mixed and filled into the outer skin, and then the powder is drawn and rolled into the flux-cored welding wire.

[0036] Preferably, the preparation method comprises the following steps:

[0037] S1. Ball-milling the formulated amount of Mn, Ca, Mo, V, Cu, Al, TiN and NiB to obtain a mixed powder, and drying and mixing the mixed powder with a slag-forming agent to obtain a medicinal powder;

[0038] S2, rolling the outer skin into a U shape, filling the powder into the U-shaped outer skin, and then drawing the outer skin to form the flux-cored welding wire.

[0039] Preferably, in step S1, the drying temperature is 70-100°C.

[0040] Preferably, in step S1, the drying time is 0.5 to 3 hours.

[0041] Preferably, in step S1, the mixing time is 30 to 40 minutes.

[0042] Preferably, in step S1, the ball milling time is 60 to 100 minutes.

[0043] Preferably, in step S2, the outer skin needs to be ultrasonically cleaned, hot-air dried, blown dry and cooled in sequence before use.

[0044] A third aspect of the present invention provides a welding method, comprising the following steps:

[0045] The flux-cored welding wire described in the first aspect of the present invention is used as the welding wire, and double-wire gas-electric vertical welding is adopted to weld marine engineering steel, and the welding heat input is ≥400kJ / cm.

[0046] Preferably, the parameters of the double-wire gas-electric vertical welding are: the welding current of the back welding wire is 390-510A, the welding voltage of the back welding wire is 36-45V, there is no swing width, and the welding speed of the back welding wire is 50-70mm / min; the welding current of the front welding wire is 401-474A, the welding voltage of the front welding wire is 39-46V, the swing width of the front welding wire is 15-20mm, and the welding speed of the front welding wire is 50-70mm / min.

[0047] Preferably, the welding heat input of the twin-wire gas-electric vertical welding is 468.6-709.6 kJ / cm, for example, it can be selected from 468.6 kJ / cm, 470 kJ / cm, 500 kJ / cm, 520 kJ / cm, 540 kJ / cm, 560 kJ / cm, 600 kJ / cm, 620 kJ / cm, 640 kJ / cm, 660 kJ / cm, 680 kJ / cm, 700 kJ / cm, 709.6 kJ / cm or any point value in the range composed of any two end points of the above.

[0048] Preferably, the welding gun angle of the twin-wire gas-electric vertical welding is 8°-12°, for example, it can be selected from 8°, 9°, 10°, 11°, 12° or any point value in the range formed by any two end points of the above.

[0049] Preferably, the marine engineering steel includes EH36 steel and EH40 steel.

[0050] Preferably, the thickness of the engineering steel is not less than 60 mm.

[0051] The fourth aspect of the present invention provides application of the flux-cored welding wire described in the first aspect of the present invention and / or the welding method described in the third aspect of the present invention in the field of welding.

[0052] The beneficial effects of the present invention are as follows: the flux-cored welding wire of the present invention, by adding NiB and TiN and adjusting the ratio of the two, can be suitable for gas-electric vertical welding with a welding heat input of ≥400 kJ / cm, which solves the problems of unstable effective inclusion particles, coarser grains, and low low-temperature toughness during ultra-large line energy welding. Under the condition of welding heat input of ≥400 kJ / cm, acicular ferrite structure can still be formed in the weld metal, and grain coarsening is effectively suppressed, which significantly improves the strength and toughness of the weld metal. After welding high-strength ship plate steel, the weld has good formability and is free of surface defects and internal pores.

[0053] The tensile strength of the weld after welding engineering steel with the flux-cored welding wire of the present invention is ≥600MPa, the yield strength is ≥400MPa, the elongation is ≥23%, the impact energy at -40°C is ≥50J, and the average grain size at the weld is 60-80μm, which can significantly improve the mechanical strength of the weld, improve the toughness at body temperature and refine the grains. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a microstructure diagram of the weld metal after welding using the flux-cored welding wire in Example 2.

[0055] Figure 2 This is a microstructure diagram of the weld metal after welding using the flux-cored welding wire in Comparative Example 1. DETAILED DESCRIPTION

[0056] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0057] Example 1

[0058] This example provides a flux-cored welding wire for super-large line energy gas electric vertical welding, which consists of an outer skin and powder, and the powder filling rate (filling rate is the ratio of the mass of powder to the total mass of powder and outer skin) is 20%, the outer skin is H08A alloy steel strip, and the outer skin is filled with powder. The diameter of the flux-cored welding wire is 1.6mm.

[0059] Taking the total mass percentage of the powder as 100%, the powder is composed of the following components in mass percentage: Mn 3.5%, Si 1.5%, Ca 0.004%, Mo 0.45%, V 0.1%, Cu 0.5%, Al 0.01%, TiN 0.4%, NiB 2.0%, rutile 1%, fluorite 0.5%, feldspar 1%, mullite 0.5%, and the balance is Fe; wherein rutile, fluorite, feldspar and mullite constitute the slag-forming agent.

[0060] The flux-cored welding wire for super-large line energy gas-electrode vertical welding in this example is prepared by a preparation method comprising the following steps:

[0061] Step S1, Mn, Si, Ca, Mo, V, Cu, Al, TiN and NiB are put into a ball mill in proportion and ball milled to obtain a mixed powder, the ball milling process parameters are set as follows: rotation speed 300 rpm, forward rotation 30 min, stop 10 min, reverse rotation 30 min, total ball milling time 70 min, ball-to-powder ratio (mass ratio of grinding balls and mixed powder) is 5:1, then the mixed powder and the slag-making agent are respectively put into a drying furnace and heated to 80° C., kept warm for 1 h, and then added to a Y-type powder mixer to mix the two for 30 min to obtain a uniformly mixed powder.

[0062] Step S2: Place the H08A steel strip into a large drying furnace, heat it to 80°C and keep it warm for 1 hour. After cooling, use a forming roller in a dust-free workshop to roll the H08A steel strip into a U shape. Then, use a powder feeding device to add the evenly mixed powder obtained in step S1 into the U-shaped outer skin according to the above powder filling rate, and then use a drawing die to roll it into a flux-cored welding wire with a diameter of 1.6 mm.

[0063] Example 2

[0064] This example provides a flux-cored welding wire for super-large line energy gas-electrode vertical welding, which consists of an outer sheath and powder, with a powder filling rate of 20%. The outer sheath is H08A alloy steel strip, and the outer sheath is filled with powder. The diameter of the flux-cored welding wire is 1.6mm.

[0065] Taking the total mass percentage of the powder as 100%, the powder is composed of the following components in mass percentage: Mn 3.5%, Si 1.7%, Ca 0.004%, Mo 0.45%, V 0.1%, Cu 0.5%, Al 0.01%, TiN 0.4%, NiB 2.4%, rutile 1%, fluorite 0.5%, feldspar 1%, mullite 0.5%, and the balance is Fe; wherein rutile, fluorite, feldspar and mullite constitute the slag-forming agent.

[0066] The flux-cored welding wire for super-large line energy gas-electrode vertical welding in this example is prepared by a preparation method comprising the following steps:

[0067] Step S1, Mn, Si, Ca, Mo, V, Cu, Al, TiN and NiB are put into a ball mill according to proportion and ball milled to obtain a mixed powder, the ball milling process parameters are set as follows: rotation speed 300 rpm, forward rotation 30 min, stop 10 min, reverse rotation 30 min, total ball milling time 70 min, ball-to-powder ratio 5:1, then the mixed powder and the slag-making agent are respectively put into a drying furnace and heated to 80° C., kept warm for 1 h, and then added into a Y-type powder mixer to mix the two for 30 min to obtain a uniformly mixed powder.

[0068] Step S2: Place the H08A steel strip into a large drying furnace, heat it to 80°C and keep it warm for 1 hour. After cooling, use a forming roller in a dust-free workshop to roll the H08A steel strip into a U shape. Then, use a powder feeding device to add the evenly mixed powder obtained in step S1 into the U-shaped outer skin according to the above powder filling rate, and then use a drawing die to roll it into a flux-cored welding wire with a diameter of 1.6 mm.

[0069] Example 3

[0070] This example provides a flux-cored welding wire for super-large line energy gas-electrode vertical welding, which consists of an outer sheath and powder, with a powder filling rate of 20%. The outer sheath is H08A alloy steel strip, and the outer sheath is filled with powder. The diameter of the flux-cored welding wire is 1.6mm.

[0071] Taking the total mass percentage of the powder as 100%, the powder is composed of the following components in mass percentage: Mn 3.5%, Si 2%, Ca 0.004%, Mo 0.45%, V 0.1%, Cu 0.5%, Al 0.01%, TiN 0.4%, NiB 2.8%, rutile 1%, fluorite 0.5%, feldspar 1%, mullite 0.5%, and the balance is Fe; wherein rutile, fluorite, feldspar and mullite constitute the slag-forming agent.

[0072] The flux-cored welding wire for super-large line energy gas-electrode vertical welding in this example is prepared by a preparation method comprising the following steps:

[0073] Step S1, Mn, Si, Ca, Mo, V, Cu, Al, TiN and NiB are put into a ball mill according to proportion and ball milled to obtain a mixed powder, the ball milling process parameters are set as follows: rotation speed 300 rpm, forward rotation 30 min, stop 10 min, reverse rotation 30 min, total ball milling time 70 min, ball-to-powder ratio 5:1, then the mixed powder and the slag-making agent are respectively put into a drying furnace and heated to 80° C., kept warm for 1 h, and then added into a Y-type powder mixer to mix the two for 30 min to obtain a uniformly mixed powder.

[0074] Step S2: Place the H08A steel strip into a large drying furnace, heat it to 80°C and keep it warm for 1 hour. After cooling, use a forming roller in a dust-free workshop to roll the H08A steel strip into a U shape. Then, use a powder feeding device to add the evenly mixed powder obtained in step S1 into the U-shaped outer skin according to the above powder filling rate, and then use a drawing die to roll it into a flux-cored welding wire with a diameter of 1.6 mm.

[0075] Example 4

[0076] This example provides a flux-cored welding wire for super-large line energy gas-electrode vertical welding, which consists of an outer sheath and powder, with a powder filling rate of 20%. The outer sheath is H08A alloy steel strip, and the outer sheath is filled with powder. The diameter of the flux-cored welding wire is 1.6mm.

[0077] Taking the total mass percentage of the powder as 100%, the powder is composed of the following components in mass percentage: Mn 3.5%, Si 2.5%, Ca 0.004%, Mo 0.45%, V 0.1%, Cu 0.5%, Al 0.01%, TiN 0.3%, NiB 2.4%, rutile 1%, fluorite 0.5%, feldspar 1%, mullite 0.5%, and the balance is Fe; wherein rutile, fluorite, feldspar and mullite constitute the slag-forming agent.

[0078] The flux-cored welding wire for super-large line energy gas-electrode vertical welding in this example is prepared by a preparation method comprising the following steps:

[0079] Step S1, Mn, Si, Ca, Mo, V, Cu, Al, TiN and NiB are put into a ball mill according to proportion and ball milled to obtain a mixed powder, the ball milling process parameters are set as follows: rotation speed 300 rpm, forward rotation 30 min, stop 10 min, reverse rotation 30 min, total ball milling time 70 min, ball-to-powder ratio 5:1, then the mixed powder and the slag-making agent are respectively put into a drying furnace and heated to 80° C., kept warm for 1 h, and then added into a Y-type powder mixer to mix the two for 30 min to obtain a uniformly mixed powder.

[0080] Step S2: Place the H08A steel strip into a large drying furnace, heat it to 80°C and keep it warm for 1 hour. After cooling, use a forming roller in a dust-free workshop to roll the H08A steel strip into a U shape. Then, use a powder feeding device to add the evenly mixed powder obtained in step S1 into the U-shaped outer skin according to the above powder filling rate, and then use a drawing die to roll it into a flux-cored welding wire with a diameter of 1.6 mm.

[0081] Example 5

[0082] This example provides a flux-cored welding wire for super-large line energy gas-electrode vertical welding, which consists of an outer sheath and powder, with a powder filling rate of 20%. The outer sheath is H08A alloy steel strip, and the outer sheath is filled with powder. The diameter of the flux-cored welding wire is 1.6mm.

[0083] Taking the total mass percentage of the powder as 100%, the powder is composed of the following components in mass percentage: Mn 3.5%, Si 2.5%, Ca 0.004%, Mo 0.45%, V 0.1%, Cu 0.5%, Al 0.01%, TiN 0.3%, NiB 2.7%, rutile 1%, fluorite 0.5%, feldspar 1%, mullite 0.5%, and the balance is Fe; wherein rutile, fluorite, feldspar and mullite constitute the slag-forming agent.

[0084] The flux-cored welding wire for super-large line energy gas-electrode vertical welding in this example is prepared by a preparation method comprising the following steps:

[0085] Step S1, Mn, Si, Ca, Mo, V, Cu, Al, TiN and NiB are put into a ball mill according to proportion and ball milled to obtain a mixed powder, the ball milling process parameters are set as follows: rotation speed 300 rpm, forward rotation 30 min, stop 10 min, reverse rotation 30 min, total ball milling time 70 min, ball-to-powder ratio 5:1, then the mixed powder and the slag-making agent are respectively put into a drying furnace and heated to 80° C., kept warm for 1 h, and then added into a Y-type powder mixer to mix the two for 30 min to obtain a uniformly mixed powder.

[0086] Step S2: Place the H08A steel strip into a large drying furnace, heat it to 80°C and keep it warm for 1 hour. After cooling, use a forming roller in a dust-free workshop to roll the H08A steel strip into a U shape. Then, use a powder feeding device to add the evenly mixed powder obtained in step S1 into the U-shaped outer skin according to the above powder filling rate, and then use a drawing die to roll it into a flux-cored welding wire with a diameter of 1.6 mm.

[0087] Comparative Example 1

[0088] This example provides a flux-cored welding wire, which is different from Example 1 in that TiN and NiB powders are not added to the flux powder.

[0089] The flux-cored welding wire in this example is composed of an outer skin and powder. The powder filling rate is 20%. The outer skin is H08A alloy steel strip, and the outer skin is filled with powder. The diameter of the flux-cored welding wire is 1.6mm.

[0090] Taking the total mass percentage of the powder as 100%, the powder is composed of the following components in mass percentage: Mn 3.5%, Si 2%, Ca 0.004%, Mo 0.45%, V 0.1%, Cu 0.5%, Al 0.01%, rutile 1%, fluorite 0.5%, feldspar 1%, mullite 0.5%, and the balance is Fe; wherein rutile, fluorite, feldspar and mullite constitute the slag-forming agent.

[0091] The flux-cored welding wire in this example was prepared by referring to the preparation method described in Example 1.

[0092] Comparative Example 2

[0093] This example provides a flux-cored welding wire, which is different from Example 1 in that only TiN powder is added to the flux powder, and no NiB powder is added.

[0094] The flux-cored welding wire in this example consists of an outer skin and powder, the powder filling rate is 20%, the outer skin is H08A alloy steel strip, and the outer skin is filled with powder. The diameter of the flux-cored welding wire is 1.6mm.

[0095] Based on the total mass percentage of 100%, the powder is composed of the following components in mass percentage: Mn 3.5%, Si3%, Ca 0.004%, Mo 0.45%, V 0.1%, Cu 0.5%, Al 0.01%, TiN 0.4%, rutile 1%, fluorite 0.5%, feldspar 1%, mullite 0.5%, and the balance is Fe; among which rutile, fluorite, feldspar and mullite constitute the slag-forming agent.

[0096] The flux-cored welding wire in this example was prepared by referring to the preparation method described in Example 1.

[0097] Comparative Example 3

[0098] This example provides a flux-cored welding wire, which is different from Example 1 in that only NiB powder is added to the flux powder, and no TiN powder is added.

[0099] The flux-cored welding wire in this example consists of an outer skin and powder, the powder filling rate is 20%, the outer skin is H08A alloy steel strip, and the outer skin is filled with powder. The diameter of the flux-cored welding wire is 1.6mm.

[0100] Taking the total mass percentage of the powder as 100%, the powder is composed of the following components in mass percentage: Mn 3.5%, Si 1%, Ca 0.004%, Mo 0.45%, V 0.1%, Cu 0.5%, Al 0.01%, NiB 2.0%, rutile 1%, fluorite 0.5%, feldspar 1%, mullite 0.5%, and the balance is Fe; wherein rutile, fluorite, feldspar and mullite constitute the slag-forming agent.

[0101] The flux-cored welding wire in this example was prepared by referring to the preparation method described in Example 1.

[0102] Performance Test:

[0103] The flux-cored welding wires prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were respectively used to weld high-strength ship plate steel (i.e., welding parent material) according to the welding parameters recorded in Table 1 below. The welding parent material was EH36 steel, and the composition of the welding parent material was shown in Table 2. The plate thickness of the welding parent material was 60 mm, and a V-shaped groove was opened after being processed into a 150 mm × 500 mm test plate, and the groove angle was 18°.

[0104] Table 1 Test welding parameters

[0105]

[0106] Table 2 Chemical composition of welding base metal

[0107]

[0108] After welding the welding base material according to the welding parameters in Table 1, the performance of the welds after welding the high-strength ship plate steel with flux-cored wire prepared in Examples 1 to 5 and Comparative Examples 1 to 3 was tested respectively, and the tensile test was carried out using a WDW-300 microcomputer-controlled electronic universal testing machine to determine the yield strength, tensile strength and elongation of each sample. The test method refers to GB / T2652-2022 "Metallic Material Weld Destructive Test Fusion Weld Joint Weld Metal Longitudinal Tensile Test". In addition, the weld metal was cut and processed into a standard Charpy-V impact specimen according to GB / T 2650-2022 "Metallic Material Weld Destructive Test Impact Test" standard. The impact test was carried out on an Instron Dynatup 9200 series drop hammer impact tester. The experimental temperature of this experiment was determined to be -40°C, and the cooling medium was ethanol. The average grain size is determined by electron backscatter diffraction, and the test method refers to the standard GB / T 38532-2020 "Determination of the average grain size by electron backscatter diffraction of microbeam analysis". The performance data measured according to the above test method are shown in Table 3 below.

[0109] Table 3 Mechanical properties test results of weld metal of Examples 1 to 5 and Comparative Examples 1 to 3

[0110] Test Group Tensile strength / MPa Yield strength / MPa Elongation % -40℃ impact energy / J Average grain diameter / μm Example 1 630 449 26 58 74.23 Example 2 670 512 26 54 79.47 Example 3 682 535 28 51 67.16 Example 4 625 419 23 53 73.41 Example 5 663 477 25 55 71.14 Comparative Example 1 530 363 20 29 110.65 Comparative Example 2 579 390 20 35 101.89 Comparative Example 3 577 387 21 36 102.13

[0111] As can be seen from Table 3, by simultaneously introducing NiB powder and TiN powder into the flux-cored welding wire in Examples 1 to 5 of the present invention, the tensile strength, yield strength, elongation and impact energy at -40°C of the welds welded with the flux-cored welding wire of the present invention can be significantly improved, and the average grain size in the welds can be significantly reduced.

[0112] The microstructures of the welds after welding the high-strength ship plate steel using the flux-cored welding wire prepared in Example 1 and Comparative Example 1 were tested by scanning electron microscopy. Figure 1 and Figure 2 As shown, compared to Figure 2 , Figure 1 The microstructure of the welded joint has a higher content of acicular ferrite, and the cross-interlocking acicular ferrite structure can effectively inhibit the propagation of cracks within the grain and improve the low-temperature toughness of the weld metal. At the same time, the acicular ferrite structure can also cut the original austenite grains, refine the effective grain size, and improve the strength of the weld metal.

[0113] In summary, the flux-cored welding wire in the present invention can be applied to gas-electric vertical welding with a welding heat input of ≥400 kJ / cm by adding NiB and TiN and adjusting the ratio of the two, and during the welding process, NiB and TiN will decompose into free [Ni], [Ti], [B], [N], wherein Ti and Ni elements can combine with O during the solidification process to form fine dispersed Ti-Ni-O, inducing the nucleation of acicular ferrite, so that there are more high-angle grain boundaries in the weld structure, resulting in a longer path during crack propagation and increased crack propagation resistance; and because the width of the acicular ferrite lath is small, the laths are closely arranged and cross-interlocked, which can significantly improve the toughness of the weld metal. The addition of Ni element is also conducive to reducing the tough-brittle transition temperature of the weld metal, thereby greatly improving the low-temperature toughness. The B element will be concentrated at the grain boundary, inhibiting the growth of the original austenite grains and the formation of grain boundary ferrite. N can combine with Al, Ti and other elements in the steel to form nitrides and re-precipitate, thereby improving the strength of the weld metal.

[0114] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A flux-cored welding wire, characterized in that: The invention comprises an outer skin and medicine powder; the medicine powder is filled in the outer skin; the medicine powder is composed of the following components in mass percentage: Mn 2.5-4.5%, Si 1-3%, Ca 0.001-0.005%, Mo 0.05-0.78%, V 0.005-0.15%, Cu 0.02-0.80%, Al 0.002-0.07%, TiN 0.3-0.55%, NiB 2.0-4.0%, slag forming agent 2.4-5.7%, and Fe as the balance.

2. The flux-cored welding wire according to claim 1, characterized in that: The material of the outer skin includes H08A alloy steel; And / or, the diameter of the flux-cored welding wire is 1-2 mm.

3. The flux-cored welding wire according to claim 1, characterized in that: The mass of the powder is 20-30% of the mass of the flux-cored welding wire.

4. The flux-cored welding wire according to claim 1, characterized in that: The slag-forming agent is selected from at least one of rutile, fluorite, feldspar and mullite.

5. The flux-cored welding wire according to claim 4, characterized in that: Taking the total mass percentage of the powder as 100%, the slag-forming agent comprises the following components in mass percentage: 1-1.4% rutile, ≤0.5% fluorite, 1-2.8% feldspar, and 0.4-1.0% mullite.

6. The method for preparing a flux-cored welding wire according to any one of claims 1 to 5, characterized in that: The following steps are involved: The raw materials of the powder are mixed and filled into the outer skin, and then the powder is drawn and rolled into the flux-cored welding wire.

7. A welding method, characterized in that: The following steps are involved: The flux-cored welding wire according to any one of claims 1 to 5 is used as welding wire, and double-wire gas-electric vertical welding is adopted to weld marine engineering steel, and the welding heat input is ≥400kJ / cm.

8. The welding method according to claim 7, characterized in that: The parameters of the double-wire gas-electric vertical welding are: the welding current of the back welding wire is 390-510A, the welding voltage of the back welding wire is 36-45V, there is no swing width, and the welding speed of the back welding wire is 50-70mm / min; the welding current of the front welding wire is 401-474A, and the welding voltage of the front welding wire is 39-46V. The swing width of the front welding wire is 15-20mm, and the welding speed of the front welding wire is 50-70mm / min; And / or, the welding heat input of the twin-wire gas-electric vertical welding is 468.6-709.6 kJ / cm; And / or, the welding gun angle of the twin-wire gas-electric vertical welding is 8°-12°.

9. The welding method according to claim 7, characterized in that: The marine engineering steel includes EH36 steel and EH40 steel.

10. Use of the flux-cored welding wire according to any one of claims 1 to 5 and / or the welding method according to any one of claims 7 to 9 in the field of welding.

Citation Information

Patent Citations

  • Matched flux-cored wire for bridge steel Q620qE

    CN109175773A

  • Flux-cored wire for ship plate steel ultra-large linear energy electro-gas welding and preparation method and application of flux-cored wire

    CN118321785A

  • Flux-cored wire with high strength, high toughness and high heat input steel and preparation method of flux-cored wire

    CN118417757A